Teoria de regularidade para equações do tipo laplaciano fracionário anisotrópico - Santos, Elisafã Braga dos (2022)
In this thesis we study integro-differential equations like the anisotropic fractional Laplacian. As in [Silvestre, Indiana Univ. Math. J. 55, 2006], we adapt the De Giorgi technique to achieve the C γ -regularity for solutions of class C 2 and use the geometry found in [Caffarelli, Leit˜ao, and Urbano, Math. Ann. 360, 2014] to obtain an ABP-type estimate, a Harnack inequality, and the interior C 1,γ regularity for viscosity solutions.